Stressing state analysis of large curvature continuous prestressed concrete box-girder bridge model - Shi, Jun; Shen, Jiyang; Zhou, Guangchun; Qin, Fengjiang; Li, Pengcheng (Journal of Civil Engineering and Management, 2019)
This paper experimentally analyzes the working behavior characteristics of a large-curvature continuous prestressed concrete box-girder (CPCBG) bridge model based on structural stressing state theory. First, the measured strain data is modeled as generalized strain energy density (GSED) to characterize the stressing state of the bridge model. Then, the Mann-Kendall (M-K) criterion is adopted to detect the stressing state leaps of the bridge model according to the natural law from quantitative change to qualitative change of a system, which derives the new definition of structural failure load. Correspondingly, the stressing state modes for the bridge model’s sections and internal forces are proposed to verify their changing characteristics and the coordinate working behavior around the characteristic loads. The analytical results reveal the working behavior characteristics of the bridge mode unseen in traditional structural analysis, which provides a new angle of view to conduct structural analysis and a reference to the improvement of design codes.